1998
DOI: 10.1111/j.1559-1816.1998.tb01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Health‐Care Allocation Decisions: A Case of Aversive Racism?

Abstract: A distributive justice framework is used to examine how individuals make judgments about what is fair when making different types of health‐care allocation decisions. The effects of 4 patient characteristics are assessed: (a) prognosis, (b) degree of responsibility for illness, (c) employment status, and (d) race. Results reveal that when the patient was defined as being more versus less responsible for his illness, respondents gave him a significantly lower priority score for obtaining health‐care services, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 11 publications
4
44
1
Order By: Relevance
“…First, the public may have more positive views of blacks suffering from health issues (i.e., that they are more deserving), in contrast to more negative perceptions of blacks on welfare. This explanation is consistent with other research that has not identified prejudicial effects in the context of health, using either an image-based racial cue (Lenton, Blair, and Hastie 2006) or text-based identification of racial group identity (Murphy-Berman, Berman, and Campbell 1998; Gollust and Lynch 2010). Second, whites may have identified the subtle race manipulation and the racialized content of the stereotype scales (e.g., “lazy”) and rated people with diabetes less negatively, to avoid violating the norm against reporting racially stereotypical opinions (Mendelberg 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, the public may have more positive views of blacks suffering from health issues (i.e., that they are more deserving), in contrast to more negative perceptions of blacks on welfare. This explanation is consistent with other research that has not identified prejudicial effects in the context of health, using either an image-based racial cue (Lenton, Blair, and Hastie 2006) or text-based identification of racial group identity (Murphy-Berman, Berman, and Campbell 1998; Gollust and Lynch 2010). Second, whites may have identified the subtle race manipulation and the racialized content of the stereotype scales (e.g., “lazy”) and rated people with diabetes less negatively, to avoid violating the norm against reporting racially stereotypical opinions (Mendelberg 2001).…”
Section: Discussionsupporting
confidence: 91%
“…In general, when people believe that a disease’s onset is controllable (or self-caused), they express less pity, convey less empathetic attitudes and more stigma toward people with that disease, and are less likely to want to help people with that disease than when they believe the disease is outside the individual’s control (Corrigan et al 2003; Ubel et al 2001; Weiner, Perry, and Magnusson 1988; Murphy-Berman, Berman, and Campbell 1998; Lenton, Blair, and Hastie 2006). These findings suggest that if people perceive the cause of diabetes to be under individuals’ control or personal responsibility (such as individuals choosing to eat unhealthily), they will be less likely to support increased spending on diabetes research.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable work in both areas supports the idea that claimants seen as responsible for their own plight are less likely to receive assistance. [17][18][19][20][21] In helping research, this finding is generally explained with reference to Bernard Weiner's 12 attributional model of motivation. In the area of distributive justice, experience allocating scarce dialysis machines in the United Kingdom 22 and the United States 7 has shown that many members of the public believe personal morality and responsibility for illness should influence how society allocates scarce life-saving technology.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the employed condition showed a pattern of results supporting an overcorrection interpretation. For priority ratings, percent of government funding, amount of personal contribution, and resentment, African-Americans received more favorable evaluations than whites (d-pooled = 1.73; Murphy-Berman, Berman, & Campbell, 1998).…”
Section: Aversive Racismmentioning
confidence: 94%